2022
DOI: 10.2147/ppa.s383269
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Family Caregiver Burden and Medication Adherence in Patients with Mechanical Valve Replacement: A Structural Equation Model

Abstract: Background: Oral anticoagulant is a necessary long-term treatment after mechanical valve replacement (MVR), and medication adherence has a great impact on patients with MVR. Although family caregiver burden is negatively correlated with medication adherence, little is known about the underlying mechanism. Purpose: To test whether family caregiver burden influences medication adherence through post-traumatic growth or medication literacy in patients with MVR. Patients and Methods: A total of 206 patients after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(77 reference statements)
3
1
0
Order By: Relevance
“…Some studies indicated that medication adherence was lower among those with financial difficulties and consideration of the medical expenses as high, which matched those observed in our study ( Liu et al, 2022 ; Drouin et al, 2023 ). Most medications for CPP are the original brands with expensive prices in China, and our study showed that 49.6% of families considered that the medication was expensive and 21.6% of them had difficulty in paying for the medical expenses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies indicated that medication adherence was lower among those with financial difficulties and consideration of the medical expenses as high, which matched those observed in our study ( Liu et al, 2022 ; Drouin et al, 2023 ). Most medications for CPP are the original brands with expensive prices in China, and our study showed that 49.6% of families considered that the medication was expensive and 21.6% of them had difficulty in paying for the medical expenses.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also found that caregivers in the poor medication adherence group had a worse cognition of the harm of noncompliance with medication, which is in agreement with Zhang et al's findings (Zhang et al, 2022). Caregivers with a lower cognition of medication adherence were more likely to present Some studies indicated that medication adherence was lower among those with financial difficulties and consideration of the medical expenses as high, which matched those observed in our study (Liu et al, 2022;Drouin et al, 2023). Most medications for CPP are the original brands with expensive prices in China, and our study showed that 49.6% of families considered that the medication was expensive and 21.6% of them had difficulty in paying for the medical expenses.…”
Section: Discussionsupporting
confidence: 85%
“…Such factors directly influence the development of PsyCap in CRC patients. In this study, there exists a significant positive association between positive PsyCap and PTG, conforming to the research among medical workers [39] and patients with mechanical valve replacement [40], further confirming the mediating role of positive PsyCap between social support and PTG of CRC patients. Based on these results, it is important for social support to affect PTG by enhancing positive PsyCap in CRC cases.…”
Section: Po 2024supporting
confidence: 90%
“…Therefore, the compliance of elderly PD patients in this centre was higher. Indeed, the caregivers' medication adherence level affects the patient's medication taking and treatment effectiveness (Muellers et al, 2019, Liu et al, 2022. However, the medication literacy and adherence levels of caregivers of PD patients are rarely reported and can be explored in future studies.…”
Section: Comparison Of Medication Adherence Among Pd Patients With Di...mentioning
confidence: 99%